Oral Presentations Abstracts: WHAT ETHICS FOR AN INCLUSIVE AGEING SOCIETY? - COBBAUT, Jean-Philippe; AIGUIER, Grégory (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Context: the ageing of the population today raises a significant number of questions to stakeholders in the health and social sectors. These questions go far beyond the questions of care to stretch out to a series of ethical problems linked to lifestyle and thus to the management of projects dedicated to the support and social inclusion of the elderly. Purpose: in this context, the way of considering the treatment of the ethical dimensions of these projects requires collaborative and reflexive governance based on the articulation between clinical ethics, organizational ethics but also – increasingly – an ethical approach of social and territorial deployment of these projects with the various stakeholders. Method: this communication will aim to present the results of two research-action studies aimed at the development and the integration of the ethical dimension in collective projects of accompaniment of elderly people within the community. Results: the conclusions do reflect the need for the collaborative and reflexive nature of the governance of the ethical approach, by emphasizing the modalities of the participation of the people concerned and the crucial stake of taking their point of view into account. of view for a relevant approach to ethics of ageing.